Towards social justice in institutions of higher learning: Addressing gender inequality in science & technology through capability approach - Kalyan Kumar Kameshwara; Tanu Shukla (Administrative Sciences, 2017)
The focus of the study is to examine and relocate gender equality in higher education using Capability Approach as the background frame. The paper discusses how gender relations are rooted in the socio-cultural matrix in India. It attempts to explore the factors prevalent in the structure which impacts woman's opportunities and functionalities in the higher education. The database includes faculty from one of the central universities of South India, the study deals with the dynamics of constructs in Science and Technology indicating socio-psychological obstructions faced by women. Based on thorough analysis, the oppressed capabilities are conceptualized thereby enabling the researchers to relocate the gender equality and the capabilities that need to be enriched for women can be contemplated which helps in reducing the existing disparity. The intention of the study is essentially not to quantify the attributes of inequality to make them measurable but to choose attributes which enable an effective comparative basis to address inequality. The empirical study reveals an existence of the element of stereotyping as a single entity and capability approach restores the uniqueness by the fractional combination of capabilities listed.
Keywords: 350; Discrimination; science and technology; stereotypes; women; capability